2013
DOI: 10.1103/physrevd.87.044002
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic quantities of a black hole with anf(R)global monopole

Abstract: The thermodynamic quantities such as the local temperature, heat capacity, offshell free energy and the stability of a black hole involving a global monopole within or outside the f (R) gravity are examined. We compare the two classes of results to show the influence from the generalization of the general relativity. It is found that the f (R) theory will modify the thermodynamic properties of black holes, but the shapes of curves for thermodynamic quantities with respect to the horizon are similar to the resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…This can lead us to find the influence of modified gravity on the thermal properties of black holes [22], for example. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…This can lead us to find the influence of modified gravity on the thermal properties of black holes [22], for example. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…whose solutions for each sign is 28) in which C 1± and C 2± are arbitrary integration constants for each sign of solution. Our calculations has shown that, the squared norms for each sign of solutions diverges, that is 29) indicating that the solutions at infinity do not belong to the Hilbert space.…”
Section: Jhep01(2014)178mentioning
confidence: 99%
“…Therein the problematic energy conditions are satisfied but at the cost of extra structures such as global monopoles [7] which pop up naturally. In a different study global monopoles were proposed as source to create the acceleration term in the weak field approximation [8].In this Letter we show that a particular f (R) gravity [9-14] with a fluid source accounts for the Rindler acceleration. The fluid satisfies the weak energy condition (WEC) and strong energy condition (SEC) in regions as depicted in Fig.…”
mentioning
confidence: 99%
“…Therein the problematic energy conditions are satisfied but at the cost of extra structures such as global monopoles [7] which pop up naturally. In a different study global monopoles were proposed as source to create the acceleration term in the weak field approximation [8].…”
mentioning
confidence: 99%